A comprehensive review of biological and genetic control approaches for leishmaniasis vector sand flies; emphasis towards promoting tools for integrated vector management. - Yasoda Kumari; Nayana Gunathilaka; Deepika Amarasinghe (PLoS Neglected Tropical Diseases)
Background Leishmaniasis is a health problem in many regions with poor health and poor life resources. According to the World Health Organization (WHO), an estimated 700,000-1 million new cases arise annually. Effective control of sand fly vector populations is crucial for reducing the transmission of this disease. Therefore, this review aims to comprehensively examine and evaluate the current methods for controlling sand fly populations, focusing on biological and gene drive techniques. Methods and findings A detailed, comprehensive literature search was carried out using databases including Google Scholar, PubMed, ScienceDirect, and the National Library of Medicine (NIH). These searches were done using specific keywords related to the field of study. This current review identified several promising methods, including genetically modified sand flies, using transgenic approaches by taking advanced gene editing tools like Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR/Cas9) and genetic modification of symbiotic microorganisms for controlling sand fly populations, which appeared to be proven under laboratory and field settings. Conclusion Genetic control approaches have many benefits over chemical control, including long-lasting effects on targets, high specificity, and less environmental impact. Advances in genetic engineering technologies, particularly CRISPR/Cas9, sterile insect techniques, and gene drive insect modification, offer new avenues for precise and efficient sand fly management. Future research should prioritize optimizing rearing and sterilization techniques, conducting controlled field trials, and fostering collaboration across disciplines to realize the potential of genetic control strategies in combating leishmaniasis.